2019
DOI: 10.1109/tifs.2019.2895552
|View full text |Cite
|
Sign up to set email alerts
|

Secret-Key Capacity Regions for Multiple Enrollments With an SRAM-PUF

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Weak PUFs provide fewer CRPs. However, these PUFs have been increasingly popular as internal key generators [28,29]. In this work, we focus on the authentication protocols that are based on strong PUFs.…”
Section: Physical Unclonable Functionmentioning
confidence: 99%
“…Weak PUFs provide fewer CRPs. However, these PUFs have been increasingly popular as internal key generators [28,29]. In this work, we focus on the authentication protocols that are based on strong PUFs.…”
Section: Physical Unclonable Functionmentioning
confidence: 99%
“…Applying multiple observations for key binding (and generation) has been studied from information-theoretic perspective in [13][14][15]. It is shown that the secret-key rate can be improved when multiple observations are used by the encoder or the decoder.…”
Section: Related Workmentioning
confidence: 99%
“…By using an additional private key, user's privacy-leakage can be made negligible [15,16]. Another scenario, that is, the BIS with one user, was extensively examined in [8,[17][18][19][20][21][22]. More precisely, in [17,18], the relation of secret-key and privacy-leakage rates was analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…The works of [8] was extended to constrain the action cost for the decoder in [20], and to consider twoenrollment systems for the same hidden source, where the encoders do not trust each other [21]. Moreover, in [22], the secret-key capacity of a multi-enrollment system, in which the decoder is required to estimate all secret keys generated in the earlier enrollments, was formulated.…”
Section: Introductionmentioning
confidence: 99%